# How do you solve 3- 2( x + 6) = - 1( x - 1) + 7?

Mar 23, 2018

$x = - 17$

#### Explanation:

$\text{distribute parenthesis on both sides of the equation}$

$3 - 2 x - 12 = - x + 1 + 7 \leftarrow \textcolor{b l u e}{\text{collect like terms}}$

$\Rightarrow - 2 x - 9 = - x + 8$

$\text{add 2x to both sides}$

$\cancel{- 2 x} \cancel{+ 2 x} - 9 = 2 x - x + 8$

$\Rightarrow - 9 = x + 8$

$\text{subtract 8 from both sides}$

$- 9 - 8 = x \cancel{+ 8} \cancel{- 8}$

$\Rightarrow - 17 = x \Rightarrow x = - 17$

$\textcolor{b l u e}{\text{As a check}}$

Substitute this value into the equation and if both sides are equal then it is the solution.

$\text{left } = 3 - \left(2 \times - 11\right) = 3 - \left(- 22\right) = 3 + 22 = 25$

$\text{right } = \left(- 1 \times - 18\right) + 7 = 18 + 7 = 25$

$\Rightarrow x = - 17 \text{ is the solution}$

Mar 23, 2018

$x = - 17$

#### Explanation:

$3 - 2 \left(x + 6\right) = - 1 \left(x - 1\right) + 7$

$3 - 2 x - 12 = - x + 1 + 7$

$- 2 x - 9 = - x + 8$

$- 9 = x + 8$

$x = - 9 - 8$

$x = - 17$